A portal to a class of novel sultone-functionalized pyridines via an annulative SuFEx process employing earth abundant nickel catalysts. Issue 65 (26th July 2018) - Chen, Xing; Zha, Gao-Feng; Fang, Wan-Yin; Rakesh, K. P.; Qin, Hua-Li
Abstract : An efficient Ni 2+ promoted process for the synthesis of a class of structurally unique heterocycles containing both pyridines and sultones was developed through a SuFEx annulation. This protocol serves as an irreplaceable asset for medicinal chemistry and drug discovery. Abstract : An efficient nickel catalyzed annulative process for the synthesis of a class of structurally unique heterocycles containing pharmaceutically important moieties of both pyridines and sultones was developed by using SuFEx chemistry. This mild and efficient method features a wide scope to serve as an irreplaceable asset for medicinal chemistry and drug discovery.